Dual-wavelength method and optoelectronic sensor for online monitoring of the efficiency of dialysis treatment. (October 2015) - Vasilevsky, A M; Konoplev, G A; Stepanova, O S; Zemchenkov, A Yu; Gerasimchuk, R P; Frorip, A
Abstract: The absorption spectra of effluent dialysate in the ultraviolet region were investigated. A novel dual-wavelength spectrophotometric method for uric acid determination in effluent dialysate and an optoelectronic sensor based on UV LED were developed. Clinical trials of the proposed sensor were carried out in the dialysis unit of St. Petersburg Mariinsky Hospital. The relative error of measurement for the concentration of uric acid does not exceed 10%.